KETIKA MEMBUNUH MENJADI SEBUAH PENYELESAIAN: Sebuah Tinjauan Fenomenologis Mengenai Tindakan Seseorang Melakukan Pembunuhan - Wahyudi, Agus (The Journal of Society and Media, 2018)
Murder is an evil action to take the soul of others. Everyone can be a murderer. Socio-culture background (age, sex, socio-enonomic, ethnic, religion) is not the reason or someone to kill others. Many factors make someone decide to kill others. One of the factors is known as killing motive. This qualitative research used the primary data. Subject were 5 people. There were 4 motives to kill, they are polygamy, money, loan, and frustration motive.